(3cJGH GdbhGajs - (3CHh GdbGSe GdJejejs
(3ChdgG (B:s
(3eG jdRe ef GdMQha hGdeMQcGJ (B: (3GdQhi hGdhUd hGdfaGP s
(3BNQgG (B:s
(3ai TQM (B" (3GdeJcGhS (B" (3hEfeG GdCUd eG cGf Ydjg HfjI GdbGajI Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(100 / 12(3b(B) s
Keywords: (3GdYQhV hGdbhGais